Negative Emission Power Plants: Thermodynamic Modeling and Evaluation of a Biomass-Based Integrated Gasification Solid Oxide Fuel Cell/Gas Turbine System for Power, Heat, and Biochar Co-Production—Part 1 - Jaiganesh, N.; Kuo, Po-Chih; Woudstra, Theo; Ajith Kumar, R.; Aravind, P. V. (Frontiers in Energy Research, 2022)
This article is the first of a two parts series presenting the thermodynamic evaluation and techno-economics of developing negative emission power plants. The aim of this research is to evaluate the potential of biochar co-production in negative emission power plants based on biomass-fed integrated gasification solid oxide fuel cell system with carbon capture and storage (BIGFC/CCS) unit.The influence of two gasification agents, namely, air and steam-oxygen on the proposed system is investigated. In Part I, we present the thermodynamic models. A sensitivity analysis is carried out to investigate system response to stepwise increase in biochar co-production (up to 10% by weight).Providing a secondary oxy-combustor in the steam-oxygen gasification case, has shown to be a solution to meet the heat requirements of the allothermal gasification process. A comprehensive exergy analysis indicated significant efficiency improvement for the steam-oxygen gasification case. The results show that the biomass steam-oxygen gasification yields the higher electrical exergy efficiency (48.3%) and combined heat and power (CHP) exergy efficiency (54.6%) for the similar rates of biochar co-production.The specific power output per unit of CO2 stored is 2.65 MW/(kg/s) and 3.58 MW/ (kg/s) for the air and steam-oxygen gasification case respectively when the biochar is co-produced at 10% by weight for the given biomass flow of 20kg/s. Moreover, the total CO2 stored due to the proposed system is calculated as 133.9 t/h and it is estimated to remove 1.17 Mt of CO2 from the atmosphere annually (when the biochar based carbon storage is also considered).The models are used for the techno-economic analysis presented in Part II of the series.